Building Post-Crisis Capacity in the Solomon Islands - Bailey, Laura (World Bank, Washington, DC, 2012)
This capacity development brief summarizes the results of a multi-donor team review of four examples of post-crisis capacity development interventions in the Solomon Islands in 2005-08 whose performance was frequently cited as successful by local stakeholders. Although not based on post-project evaluations, the review found a number of patterns and potential lessons: (1) responding to immediate needs fosters national ownership; (2) 'quick wins' can lay the basis for wider system impact; (3) being clear on 'capacity for what' is key to project success, (4) critical mass in capacity means taking a team approach; (5) training must be grounded in time-relevant and actively operational tasks; (6) a coaching and partnering style is essential and, certainly, not optional; and (7) leadership becomes catalytic in capacity development when a broader coalition is engaged, and in some cases supports a 'heroic individual' as its leader.